Aaron Ember and the Establishment of Egypto-Semitic Phonological and Lexical Comparison (Part II) - Takács, Gábor (Acta Orientalia Vilnensia, 2006)
Institute of Linguistics, Hungarian Academy of Science, Eötvös Loránd University The present paper represents the second half of the appraisal of Aaron Ember’s contribution to Egypto-Semitic etymology. The first part was introduced by a sketchy biography of Ember and an overview of his conception of Egypto-Semitic sound correspondences, which was followed by the analysis and evaluation of those Egypto-Semitic etymologies proposed by Ember that have to be either abandoned or complemented in the testimony of current progress in Afro-Asiatic linguistic comparison. For technical reasons, this list was restricted to the Egyptian roots with 3- to p- in Anlaut. This is why the following etymological material encompasses Egyptian roots with m- to d-.